2021
DOI: 10.1111/obr.13364
|View full text |Cite
|
Sign up to set email alerts
|

Modulating eating behavior with transcranial direct current stimulation (tDCS): A systematic literature review on the impact of eating behavior traits

Abstract: Transcranial direct current stimulation (tDCS) is becoming an increasingly popular technique for altering eating behaviors. Recent research suggests a possible eating behavior trait-dependent effect of tDCS. However, studies recruit participant populations with heterogeneous trait characteristics, including "healthy" individuals who do not present with eating behavior traits suggesting susceptibility to overconsumption. The present review considers the effects of tDCS across eating-related measures and explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 113 publications
(381 reference statements)
0
7
0
Order By: Relevance
“…The patient examined by us did not report any severe adverse effects. More studies confirm the safety and tolerability of brain stimulation [21]. Most reports of problems after stimulation were: itching, burning sensation and headache.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The patient examined by us did not report any severe adverse effects. More studies confirm the safety and tolerability of brain stimulation [21]. Most reports of problems after stimulation were: itching, burning sensation and headache.…”
Section: Discussionmentioning
confidence: 69%
“…The systematic review indicates not enough promising evidence of brain stimulation in AN to implement them in clinical practice [13]. Some reports indicate none, while other improvements in BMI after tDCS [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the practical inclusion criteria and challenges related to the COVID pandemic, our sample group comprised of moderate craving subjects. Studies have shown that eating behavior traits significantly predict tDCS effectiveness ( Beaumont et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, an effect is more consistently shown in those with frequent food cravings or binge-type behaviors (6,7,41,42,45,46). This highlights a potential behavior trait-dependent effect of tDCS (62). Novel target locations include the right inferior frontal gyrus (43,44), medial prefrontal cortex (48), right extrastriate body area (48), and the primary motor cortex representation of the tongue muscle (57) (Figure 1).…”
Section: Montagementioning
confidence: 99%